2016
DOI: 10.1007/s11356-016-7390-x
|View full text |Cite
|
Sign up to set email alerts
|

Technical feasibility study of a low-cost hybrid PAC-UF system for wastewater reclamation and reuse: a focus on feedwater production for low-pressure boilers

Abstract: This study has applied the concept of the hybrid PAC-UF process in the treatment of the final effluent of the palm oil industry for reuse as feedwater for low-pressure boilers. In a bench-scale set-up, a low-cost empty fruit bunch-based powdered activated carbon (PAC) was employed for upstream adsorption of biotreated palm oil mill effluent (BPOME) with the process conditions: 60 g/L dose of PAC, 68 min of mixing time and 200 rpm of mixing speed, to reduce the feedwater strength, alleviate probable fouling of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Addition of PAC provided reduced membrane fouling. The studies showed that the addition of PAC to membrane systems helped to slow down the membrane fouling rate by reducing the deposition of biofoulants such as extracellular polymeric substance (EPS) and organic matter on the membrane surface (Amosaet al, 2016a;Amosa et al, 2016b;Kaya et al, 2016). The treatability of this wastewater with aerobic membrane reactors in terms of organic load and etodolac content was studied (Kaya et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Addition of PAC provided reduced membrane fouling. The studies showed that the addition of PAC to membrane systems helped to slow down the membrane fouling rate by reducing the deposition of biofoulants such as extracellular polymeric substance (EPS) and organic matter on the membrane surface (Amosaet al, 2016a;Amosa et al, 2016b;Kaya et al, 2016). The treatability of this wastewater with aerobic membrane reactors in terms of organic load and etodolac content was studied (Kaya et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Governing equations for constant pressure and constant flux separations in the interstices of a membrane are used for evaluation of the reduced pore size, maximum filtrate volume, and fouling potential (Iritani, 2013). Amosa et al (2016) conducted fouling studies on a Newtonian fluid (biotreated POME) using three different ultrafiltration membranes with different molecular weight cut-offs (MWCOs). They measured the extent of fouling using blocking index, which is a dimensionless filtration constant that characterizes the type of fouling model, comprising of four steps of complete blocking, standard blocking, intermediate blocking, and cake filtration, corresponding to a blocking index from 2 to 0.…”
Section: Das Et Almentioning
confidence: 99%
“…Membrane processes, like microfiltration, also have the potential to recover surfactants from the oil and grease content of steel sludges, which will invariably help in process economics. Amosa et al (2016) evaluated the technical feasibility of a cost effective integrated PAC ultrafiltration bench scale scheme, for facilitating water recovery in the final step of effluent treatment in the palm oil sector. They used a waste fruit bunch to derive the adsorbent for upstream treatment, followed by downstream management in a cross flow polyethersulfone ultrafiltration membrane system comprising of ultrafiltration membranes with three different MWCOs of 1, 5, and 10 kDa.…”
Section: Das Et Almentioning
confidence: 99%
“…Concentrations of critical constituents were below the recommended values. Amosa et al (2016b) investigated the technical feasibility of using a low-cost hybrid PAC and ultrafiltration (UF) to produce feed water for low-pressure boilers from POME that had been biodegraded through an anaerobic and/or aerobic process. It was found that the permeate qualities of boiler-feed and cooling water that was filtered with a polyethersulfone membrane met the US EPA reuse standard.…”
Section: Treatment Technologymentioning
confidence: 99%